(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Anabaena sp. are the dominant cyanobacterial species on terracotta monuments of Bishnupur which exposed to high solar radiation, ultraviolet and in a desiccated condition in most part of the year. In the present study three Anabaena species were isolated from crust samples and its antibacterial activities were evaluated against pathogenic bacteria Bacillus subtilis, Listeria monocytogenes, Staphylococcus aureus, Salmonella typhimurium, Escherichia coli. We observed good antibacterial activity in ethyl acetate and ethanol extract of Anabaena sp. (VBCCA 052002) which having highest antibacterial activity against Staphylococcus aureus, Salmonella typhimurium, Staphylococcus aureus and E. coli respectively. We have validated the antibacterial assay by using resazurin based antimicrobial assay in microtiter plates and calculated the MIC value of ethyl acetate extract of Anabaena sp. (VBCCA 052002) which is found to be 100 µg/ml against Staphylococcus aureus and 150 µg/ml against Salmonella typhimurium.